Starvation and refeeding influence the growth, biochemical index, intestinal microbiota, and transcriptomic profiles of golden pompano Trachinotus ovatus (Linnaeus 1758) - Liu, Bo; Guo, Hua-Yang; Liu, Bao-Suo; Zhang, Nan; Yang, Jing-Wen; Guo, Liang; Jiang, Shi-Gui; Zhang, Dian-Chang (Frontiers in Marine Science, 2022)
Starvation is a common stress in fish that is caused by environmental changes, and refeeding after starvation is believed to cause compensatory growth. Here, we evaluated the impacts of starvation for 7 d, followed by refeeding for 7 d on growth, gut microbiome, biochemical indices, liver transcriptome, and immune response in golden pompanos (Trachinotus ovatus). Starvation induced hypoglycemia, reduced triglyceride concentration, and considerably affected the activities of glycolysis related enzymes, including glucokinase (GK), pyruvate kinase (PK), and fructokinase 6-phosphate (PFK). Additionally, starvation for 7 d increased the concentrations of oxidative stress indicators, including cortisol (COR), superoxide dismutase (SOD), malondialdehyde (MDA), and catalase (CAT) and non-specific immunity parameters, including alkaline phosphatase (ALP), acid phosphatase (ACP), and lysozyme (LYZ). parameters to normal levels. Moreover, starvation affected the diversity and composition of the intestinal microbiota of T. ovatus. At the phylum level, the dominant phyla were Proteobacteria, Spirochaetes, and Tenericutes, while the dominant genera were Brevinema, Haematospirillum, and Mycoplasma. Transcriptome analysis of liver tissues showed that the mRNA expression of GK, PK, and PFK, were altered by starvation, and the trends were consistent with the activity levels of the enzymes. A total of 2,287 DEGs were identified among the control, starvation, and refeeding groups. DEGs in starvation (ST7) vs. control (CK) groups were mainly involved in cell cycle, DNA replication, and mitosis, whereas those in the refeeding (RT7) vs. ST7 groups were associated with stimulus responses and carbohydrate metabolism. Overall, most starvation-induced changes in enzyme activity, intestinal microbiome, immune response, and liver transcriptome were gradually restored to normal after refeeding for 7 d. These data provide a theoretical reference for the farming of T. ovatus during periods of feed scarcity.